Clinal variation in freezing tolerance among natural accessions of Arabidopsis thaliana - Zhen, Ying (The New phytologist, 2008)
Low temperature represents a form of abiotic stress that varies predictably with latitude and altitude and to which organisms have evolved multiple physiological responses. Plants provide an especially useful experimental system for investigating the ecological and evolutionary dynamics of tolerance to low temperature because of their sessile lifestyle and inability to escape ambient atmospheric conditions. Here, intraspecific variation in freezing tolerance was investigated in Arabidopsis thaliana by conducting freezing tolerance assays on 71 accessions collected from across the native range of the species. Assays were performed at multiple minimum temperatures and on both cold-acclimated and non-cold-acclimated individuals. Considerable variation in freezing tolerance was observed among accessions both with and without a prior cold-acclimation treatment, suggesting that differences among accessions in cold-acclimation capacity as well as differences in intrinsic physiology contribute to variation in this phenotype. A highly significant positive relationship was observed between freezing tolerance and latitude of origin of accessions, consistent with a major role for natural selection in shaping variation in this phenotype. Clinal variation in freezing tolerance in A. thaliana coupled with considerable knowledge of the underlying genetics and physiology of this phenotype should allow evolutionary genetic analysis at multiple levels